In situ synthesis of ZnO/g-C3N4 based composites for photodegradation of methylene blue under visible light - S. Pourali; R. Amrollahi; S. Alamolhoda; S. M. Masoudpanah (Scientific Reports)
Abstract In this study, in situ-synthesized ZnO/g-C3N4 based composites were used as photocatalysts for organic pollution removal. These nanocomposites were prepared through simple calcination of a mixture of melamine and ZnO nanoparticles and underwent comprehensive evaluation of their structural, morphological, optical, and photocatalytic properties, using various analytical techniques. As the g-C3N4 content increased, the band gap decreased from 3.02 to 2.94 eV. Additionally, the reduction in photoluminescence intensity confirmed the heterojunction interface between the g-C3N4 and ZnO components. The photodegradation rate of methylene blue (MB) dye exhibited an increase, rising from 0.016 (min−1) for ZnO and 0.011 (min−1) for g-C3N4 to 0.022 (min−1) for the ZnO/g-C3N4 (10 wt%) composite. Furthermore, combining ZnO (50 wt%) with g-C3N4 led to a significant enhancement in the MB dye removal efficiency, reaching 97% compared to the ZnO/g-C3N4 (10 wt%) composite. In contrast, the removal efficiencies were 90% for pristine ZnO and 73% for g-C3N4 phases.